Food regulation : law, science, policy, and practice - Fortin, Neal D., 4 0 16; 5 (Hoboken, New Jersey : John Wiley & Sons, Inc., 2017)
Featuring case studies and discussion questions, this textbook -- with revisions addressing significant changes to US food law -- offers accessible coverage appropriate to a wide audience of students and professionals. Overviews the federal statutes, regulations, and regulatory agencies concerned with food regulation and introduces students to the case law and statutory scheme of food regulation. Focuses updated content on the 2011 FDA Food Safety Modernization Act (FSMA), the biggest change to US food law since the 1930s. Contains over 20% new material, particularly a rewritten import law chapter and revisions related to food safety regulation, health claims, and food defense. Features case studies and discussion questions about application of law, policy questions, and emerging issues--;This text provides an accessible guide to United States food regulation -- essential information for anyone not only studying or involved with the US food industry, but also internationally for exporting food to the US market--
Title Page; Copyright; Dedication; About the Author; Foreword; Preface; Acknowledgments; Part I: Introductory Chapters; Chapter 1: Introduction to Food Regulation in the United States; 1.1 Introduction; 1.2 A Short History of Food Regulation in the United States; 1.3 The U.S. Legal System; 1.4 Agency Procedural Regulation; 1.5 Agency Jurisdiction; 1.6 Major Federal Laws; 1.7 Informational Resources; Chapter 2: What Is Food?; 2.1 Introduction to the Food, Drug, and Cosmetic Act; 2.2 What Makes an Article a Food or a Drug?; 2.3 The Central Role of Intended Use; 2.4 Other Considerations.;Part II: Regulation of Labeling, Advertising, and ClaimsChapter 3: Food Labeling; 3.1 Introduction; 3.2 Legal Authorities; 3.3 Labeling Terminology; 3.4 Affirmative Label Requirements; 3.5 Misbranded Food: Prohibited Representations; 3.6 Deceptive Packaging; 3.7 Warning Statements; 3.8 Allergens; 3.9 Alcoholic Beverages; 3.10 USDA FSIS; Chapter 4: Nutritional Labeling and Nutrient Level Claims; 4.1 Introduction; 4.2 The Nutrition Labeling and Education Act (NLEA); 4.3 The Nutrition Facts Panel; 4.4 Trans Fats; 4.5 NLEA and Restaurants; 4.6 Menu and Vending Machine Labeling Requirements.;4.7 Nutrient Content Claims (Nutrient Level Descriptors)Chapter 5: Health Claims; 5.1 Background; 5.2 Definitions; 5.3 Health-Related Claims That Are Not Health Claims; 5.4 Preapproved Health Claims (NLEA); 5.5 Authoritative Statements: FDA Modernization Act; 5.6 Qualified Claims; 5.7 Substantiation of Claims; 5.8 Therapeutic and Related Disease Claims; Chapter 6: Credence Claims and Conditional Labeling; 6.1 Introduction; 6.2 Country of Origin Labeling; 6.3 Organic Foods; 6.4 Natural Claims; 6.5 Religious Certification Marks and Symbols; 6.6 Geographic Indications.;6.7 USDA Process Verified (Figure 6.4)6.8 Conditional Claims and Marks; Chapter 7: Advertising and Other Regulation of Labeling; 7.1 Introduction; 7.2 Federal Trade Commission; 7.3 Other Regulatory Considerations with Advertising; 7.4 Competitor Challenges; Part III: Regulation of the Composition of Food; Chapter 8: Economic and Aesthetic Adulteration; 8.1 Introduction; 8.2 Food Standards: Regulation of Food Identity and Quality; 8.3 Economic Adulteration; 8.4 Sanitation and Aesthetic Adulteration; Chapter 9: Regulation of Unintentional Poisonous or Deleterious Substances in Food.;9.1 Introduction9.2 Pesticide Residues; 9.3 Environmental Contaminants; 9.4 Specific Food Safety Rules; 9.5 Science-Based, Risk-Control Plans; 9.6 FSMA Hazard Analysis and Preventive Control (HARPC) Plans; 9.7 Produce Safety Standards; 9.8 Additional Food Safety Performance Standards; 9.9 Reportable Food Registry; Chapter 10: Regulation of the Safety of Intentional Components of Food: Food Additives, Food Colorings, and Irradiation; 10.1 Introduction; 10.2 Background; 10.3 Food Additives; 10.4 Prior Sanctioned Substances; 10.5 GRAS (Generally Recognized as Safe); 10.6 Indirect Additives; 10.7 Some Controversial Food Additives and Substances.
Includes bibliographical references and index.
Print version record.
Keywords: 2 -- 0; 6; Safety regulations;Food Science.;Agriculture & Food.;Administrative Law & Regulatory Practice.;Safety regulations. -- Food law and legislation;Food industry and trade;Food adulteration and inspection;TECHNOLOGY & ENGINEERING;SOCIAL SCIENCE;LAW;Food adulteration and inspection.;Food industry and trade;Food law and legislation. -- United States.;United States.;United States; United States; Electronic books. -- 2